Reviews of Physiology, Biochemistry and Pharmacology, Vol. 175 (Reviews of Physiology, Biochemistry and Pharmacology,, 2018)
Gabriel A. Aguirre, José Luis González-Guerra, Luis Espinosa, Inma Castilla-Cortazar: Insulin-Like Growth Factor 1 in the Cardiovascular System Farzad Khademi, Ramezan Ali Taheri, Amir Abbas Momtazi-Borojeni, Gholamreza Farnoosh, Thomas P. Johnston, Amirhossein Sahebkar: Potential of cationic liposomes as adjuvants/delivery systems for tuberculosis subunit vaccines Theerut Luangmonkong, Su Suriguga, Henricus A. M. Mutsaers, Geny M. M. Groothuis, Peter Olinga, Miriam Boersema: Targeting Oxidative Stress for the Treatment of Liver Fibrosis.